THE HUMAN TRAGEDY IN JACK LONDON’S NOVEL “MARTIN EDEN” - Aralova Lobar (TADQIQOTLAR, 2025)
Abstract:  Literary  interpretation  of  social  psychology  in  the  novel  “Martin Eden” is analyzed in the article.